What Can Be Said: The Jenő Janovics Archive in Cluj - TOMPA, Andrea (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
This paper focuses on the documents kept in archive of Jenő Janovics, an artistic director in Hungary and Romania for 30 years. The rich archival materials, kept in Cluj, of this important public figure reflect the turbulent times of history of Hungarian Theater in Cluj in the first half of the 20th century. The study presents a possible approach to this material, also introducing Janovics’s diary’s hermeneutical problems.